La casa de enfrente - Figueroa, Ray; Rodríguez, Manolito; Cruz, Yuliet (Casa Comal Cine, 2003)
When conducting an audit, Angel discovers a millionaire diversion of national funds. His moral conflict between taking or not taking the bribe offered to him, takes us through the scenario of power, money and marginality. It is then when Angel, close to getting married, meets a Caribbean emigrant who aspires to travel to the United States.